Laser-Assisted aPDT Protocols in Randomized Controlled Clinical Trials in Dentistry: A Systematic Review - Valina Mylona; Eugenia Anagnostaki; Steven Parker; Mark Cronshaw; Edward Lynch; Martin Grootveld (MDPI AG, 2020)
Background: Antimicrobial photodynamic therapy (aPDT) has been proposed as an effective alternative method for the adjunctive treatment of all classes of oral infections. The multifactorial nature of its mechanism of action correlates with various influencing factors, involving parameters concerning both the photosensitizer and the light delivery system. This study aims to critically evaluate the recorded parameters of aPDT applications that use lasers as the light source in randomized clinical trials in dentistry. Methods: PubMed and Cochrane search engines were used to identify human clinical trials of aPDT therapy in dentistry. After applying specific keywords, additional filters, inclusion and exclusion criteria, the initial number of 7744 articles was reduced to 38. Results: Almost one-half of the articles presented incomplete parameters, whilst the others had different protocols, even with the same photosensitizer and for the same field of application. Conclusions: No safe recommendation for aPDT protocols can be extrapolated for clinical use. Further research investigations should be performed with clear protocols, so that standardization for their potential dental applications can be achieved.